2023
DOI: 10.1039/d3ra00648d
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the mechanism of water oxidation catalyzed by a mononuclear copper complex: important roles of a redox non-innocent ligand and HPO42−anion

Abstract: DFT calculations suggest the redox non-innocent role of the ligand and proton-accepting role of HPO42− are beneficial for the water oxidation catalyzed by a mononuclear copper complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 62 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Firstly, a water molecule coordinating with the Cu center of the Cu II complex generates the complex of Cu II -H 2 O. This complex undergoes two proton-coupled electron transfer processes to produce an intermediate (•L-Cu II -O•), which can be described as a Cu II [258] with permission from the Royal Society of Chemistry.…”
Section: Cu Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, a water molecule coordinating with the Cu center of the Cu II complex generates the complex of Cu II -H 2 O. This complex undergoes two proton-coupled electron transfer processes to produce an intermediate (•L-Cu II -O•), which can be described as a Cu II [258] with permission from the Royal Society of Chemistry.…”
Section: Cu Complexesmentioning
confidence: 99%
“…Atomically dispersed Ir atoms incorporated into spinel Co3O4 lattice as an acidic OER catalyst were reported to exhibit excellent activity and stability for water oxidation. FTIR observation of *OOH indicates that the AEM rather than the LOM dominates the OER [258] with permission from the Royal Society of Chemistry.…”
Section: Single-atom Catalysts (Sacs)mentioning
confidence: 99%
“…The mechanism of OER catalyzed by a mononuclear Cu complex in alkaline conditions was studied by DFT calculations and shown in Figure 18. Firstly, a water molecule coordinating with the copper center of the complex of Cu II generates the complex of Cu II -H2O which undergoes two proton- [258] with permission from the Royal Society of Chemistry.…”
Section: Cu Complexesmentioning
confidence: 99%
“…31 Furthermore, the incorporation of a redox-active ligand introduces additional intricacies into the reaction mechanism, with the single electron transfer-water nucleophilic attack (SET-WNA) mechanism commonly proposed for mononuclear Cu-based complexes. [32][33][34][35][36] Additionally, under the influence of redox-active ligands, recent studies have indicated that the copper center even exhibits redox inertness, maintaining consistent oxidation states for various intermediates throughout the catalytic cycle. Given the complexities at the mechanistic level, it is crucial to elucidate the reaction mechanism of Cu-based water oxidation catalysts through theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexities at the mechanistic level, it is crucial to elucidate the reaction mechanism of Cu-based water oxidation catalysts through theoretical calculations. 26,27,29,33 These insights offer valuable information for the future design and development of novel copper-based water oxidation catalysts (WOCs).…”
Section: Introductionmentioning
confidence: 99%